The Customer Relationship Management Concept Increases Customer Commitment - Widiya Putri Nurani; Nuriadi Manurung; Muthia Dewi (ITEJ (Information Technology Engineering Journals), 2025)
The advancement of information technology has encouraged business actors, including retail enterprises such as Toko Jaya Fashion, to adopt digital strategies in order to maintain and enhance customer commitment. Toko Jaya Fashion still operates using a manual sales system, resulting in low efficiency in customer data management and a noticeable decline in sales, particularly at the end of 2024. This study employs a qualitative research method by observing a single case in detail. This approach allows the researcher to gain a comprehensive understanding of the issues studied. This study aims to design and implement a web-based Customer Relationship Management (CRM) system as a solution to address these issues. The system is developed using the PHP programming language and MySQL database, and is equipped with features such as member cards, cashback programs, monthly sales reports, and online customer service. Based on the implementation results, the system significantly improves service quality, broadens marketing reach, and assists in managing customer data in a structured manner. It provides easier access to product information, offers special promotions for loyal customers, and facilitates customer feedback through WhatsApp integration. Moreover, the adoption of this CRM website has expanded product sales to customers outside the Meranti area, enabling Toko Jaya Fashion to reach more customers and increase overall satisfaction, thereby strengthening customer commitment.